Biological impact of nanodiamond particles – label free, high-resolution methods for nanotoxicity assessment. Issue 9 (21st October 2019) - Khanal, Dipesh; Zhang, Fan; Song, Yang; Hau, Herman; Gautam, Archana; Yamaguchi, Seiji; Uertz, Jamie; Mills, Stewart; Kondyurin, Alexey; Knowles, Jonathan C.; Georgiou, George; Ramzan, Iqbal; et al.
Abstract: Current methods for the assessment of nanoparticle safety that are based on 2D cell culture models and fluorescence-based assays show limited sensitivity and they lack biomimicry. Consequently, the health risks associated with the use of many nanoparticles have not yet been established. There is a need to develop in vitro models that mimic physiology more accurately and enable high throughput assessment. There is also a need to set up new assays that offer high sensitivity and are label-free. Here we developed 'mini-liver' models using scaffold-free bioprinting and used these models together with label-free nanoscale techniques for the assessment of toxicity of nanodiamond produced by laser-assisted technology. Results showed that NDs induced cytotoxicity in a concentration and exposure-time dependent manner. The loss of cell function was confirmed by increased cell stiffness, decreased cell membrane barrier integrity and reduced cells mobility. We further showed that NDs elevated the production of reactive oxygen species and reduced cell viability. Our approach that combined mini-liver models with label-free high-resolution techniques showed improved sensitivity in toxicity assessment. Notably, this approach allowed for label-free semi-high throughput measurements of nanoparticle-cell interactions, thus could be considered as a complementary approach to currently used methods.